Domesticating the West : the re-creation of the nineteenth-century American middle class - Jackson, Brenda K. (Women in the West., 2005)
"In 1881 Thomas and Elizabeth Tannatt said a final good-bye to Massachusetts and the eastern seaboard and set out in search not of land but of opportunities for social and political advancement. Facing severe limitations to their goals in the depressed and disheveled postwar East, the Tannatts went west to Walla Walla, Washington Territory, to pursue their dreams of influence and status." "Domesticating the West examines the motivations of late nineteenth-century middle-class migrants who moved west to build communities and establish themselves as leaders. The West offered new opportunities for solidly middle-class eastern families who endured hardship, uncertainty, and displacement during the Civil War, and who struggled to carve out meaningful social space in the war's aftermath. Brenda K. Jackson places the Tannatts at the center of this movement and demonstrates how gender, class, and place affected the new migrants' abilities to integrate into their new communities. She also shows how easterners redefined themselves as leaders of a new, moral western environment through volunteerism and political participation. While many studies of westward expansion focus exclusively on the earliest pioneers, Jackson adroitly shows how later arrivals shaped the social, economic, and cultural growth of the nation."--Jacket